DETERMINASI PERMINTAAN ENERGI DOMESTIK DAN KAPASITAS KILANG TERHADAP IMPOR MIGAS DI INDONESIA - Tri Vadma Aura; M. Ridwansyah; Nuriah Alfisyahri (STKIP Subang, 2026)
This study is entitled “The Determinants of Domestic Energy Demand and Refinery Capacity on Oil and Gas Imports in Indonesia.”. This study aims to analyze the effect of domestic energy demand and refinery capacity on oil and gas imports in Indonesia and to identify the most dominant factor influencing them. The study is motivated by the increasing national energy demand that cannot be fully met by domestic oil and gas production and refining capacity, resulting in Indonesia's dependence on oil and gas imports. This research employs a quantitative approach using multiple linear regression analysis. The variables used consist of domestic energy demand and refinery capacity as independent variables, while oil and gas imports serve as the dependent variable. The results show that domestic energy demand and refinery capacity significantly affect oil and gas imports in Indonesia. Refinery capacity is the most dominant factor influencing oil and gas imports. Limited domestic refining capacity has not been able to optimally meet national energy needs, thereby increasing dependence on oil and gas imports.